A pre-COVID case of multisystem inflammatory syndrome leading to fatal outcomes in a young woman - Barua, Mousumi (Indian Journal of Case Reports, 2025)
Multisystem inflammatory syndrome (MIS) in adults involves severe complications, which include cardiovascular, cerebrovascular, and neural systems, in response to viral infections or vaccines. In this report, we describe a MIS-like clinical picture long before the COVID-19 pandemic in a 32-year-old woman, who was initially diagnosed with reactive sacroiliitis and soon after with myositis. After about 2 months, the patient developed dilated cardiomyopathy and congestive heart failure, leading to stroke. Brain imaging revealed an increased left middle cerebral artery infarct, increased midline shift, and right basal ganglia bleed, requiring decompressive craniectomy and mechanical ventilation. The patient became unresponsive and comatose and was discharged from the hospital at the family’s request. During about 2 months of home care, the patient continued to be in a deep coma, developed bedsores over the body and gangrene of her lower limbs, and eventually died. This tragic case highlights the necessity of intense monitoring and assessments that should lead to early and accurate diagnosis, coupled with concurrent and prophylactic treatments to avoid fatal complications due to disease cascades following an MIS-like clinical syndrome.